Folate contraception and clinical practice - Vera N. Prilepskaya (Гинекология, 2020)
Since the first pill, there has been a significant evolution of hormonal contraception: low- and micro-dose drugs have appeared, drugs with components as close as possible to endogenous hormones have been developed, new dosage regimens and routes of contraceptive administration have been created. Modern combined oral contraceptives are not only used to prevent unwanted pregnancies, but are also widely used to treat a number of gynecological and non-gynecological diseases. In recent years, two new combined oral contraceptives with folate supplementation have been developed. The main purpose of adding folate to contraceptives is the prevention of fetal malformations, which is ensured by an increase in the level of folate in the body of women of reproductive age against the background of contraception and after its withdrawal.